USE OF PUZZLE MEDIA IN LEARNING PAI - Sabariah Lubis (CV. Asry Persada Quality, 2024)
The purpose of this article is to analyze the use of puzzle media in Islamic Religious Education learning. This study uses the library research method. In the learning process, the use of media is inseparable from increasing the effectiveness of learning, both general learning and Islamic Religious Education learning. One of the media that can be used by teachers is puzzle media because this media can increase students' interest and motivation to learn. Puzzle learning media is a simple media that is played by disassembling and reassembling. This media is a learning media that uses puzzle game techniques to sharpen the brain. Puzzles consist of boards and several pieces, which when arranged will cover the part of the board that is slightly indented and will become a certain shape. The purpose of using this learning media itself is to make it easier for students to master the learning competencies that have been set, so that the use of puzzle media in the Islamic Religious Education learning process can be more effective and enjoyable.